Optimalisasi Peran Dosen Kebidanan dalam Edukasi Catin tentang Pencegahan Stunting Sejak Pra Nikah di Wilayah Binaan BP4 - Hilda Prajayanti; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Stunting is a chronic nutritional problem that has long-term impacts on the quality of human resources. Prevention efforts must begin before pregnancy, including during the premarital period. Midwifery lecturers have a strategic role in providing education on reproductive health and nutrition. This community service activity aims to optimize the role of midwifery lecturers in educating prospective brides and grooms about stunting prevention before marriage in the BP4-assisted area. The methods used include lectures, interactive discussions, and the distribution of educational materials. Results showed an increase in knowledge among participants regarding nutrition, reproductive health, and readiness for parenthood. Midwifery lecturers proved to be effective agents of change in reducing the risk of stunting from the upstream. Cross-sectoral support is needed to ensure the sustainability of this program.